GADGET ADDICTION AND CHANGES IN SOCIAL INTERACTIONS AMONG EARLY CHILDHOOD CHILDREN IN BETUNGAN, BENGKULU CITY - Putri, Sonnya Desvi Hartati Isaya; Safitra, Linda; Susiyanto (Program Studi Sosiologi Universitas Malikussaleh, 2025)
This study aims to examine the impact of gadget addiction on changes in the social interactions of early childhood children in Betungan Village, Bengkulu City. Using a qualitative approach and case study method, data was collected through in-depth interviews and documentation, analyzed using theory of social change and symbolic interaction. The results of the study show that, on average, children spend more than four hours per day using gadgets, far exceeding the one hour limit recommended by experts. This habit has led to a decline in children's participation in group play, difficulties in understanding emotional expressions, and limitations in two-way communication. Passive stimulation from screens replaces physical activity and creative play, which are essential for fine motor development and imagination, thereby hindering socio-emotional growth. The main factors contributing to addiction include easy access to gadgets at home, app designs that make it difficult for children to detach, and a lack of alternative educational and recreational activities. In addition, the use of gadgets as a distraction tool in parenting reduces face to face interaction and emotional closeness between parents and children. A collaborative effort between families, educational institutions, and local governments is needed to set screen time limits, provide child friendly play facilities, and develop interactive stimulation programs to mitigate the negative effects of gadget addiction on the social, emotional, and cognitive development of early childhood.